Perceived coaching behaviors in wrestling - Tzioumakis, Y.; Michalopoulou, M.; Barbas, I.; Karamanis, E. (International Journal of Wrestling Science, 2011)
The purpose of the present study was to determine the internal consistency and the reliability of the scales of Coaching Behavior Assessment System - Perceived Behavior Scale (CBAS-PBS) when using the Greek version (Gr-CBAS-PBS) with athletes and coaches in Greco-Roman wrestling. A secondary purpose was to determine the degree to which athletes` perceptions about their coaches` behaviors correlate with coaches` perceptions about their own behavior. Participants in this study were 105 male Greco-Roman wrestling athletes (M = 25.8, SD = 5,3 years) and their experience in competitive wrestling was 11.34 (SD = 5.68 years). Additionally, 21 male Greco-Roman wrestling coaches (M = 44.9, SD = 12.8 years) participated in this study and their experience in competitive wrestling was 14.9 (SD = 11.3 years). Analysis of data revealed that GR-CBAS-PBS items have good internal consistency (á = .86). Calculation of intraclass correlations using a 2-way random variable absolute agreement approach generated an average ICC (2,1) of .77 for athletes (ranging from .55 to .98) and of .70 for coaches (ranging from .55 to .91). Additionally, results revealed a strong correlation (r =.81, p>.01) between the coaches` perceptions of their own behaviors and athletes` perceptions of their coaches` behaviors. In conclusion the results of the study revealed moderate to substantial psychometric properties of the scale. Therefore, the scale could be used in the Greek wresting population to categorize perceptions of coaching behaviors.